Monogenic cerebral small‐vessel diseases: diagnosis and therapy. Consensus recommendations of the European Academy of Neurology. (20th March 2020) - Mancuso, M.; Arnold, M.; Bersano, A.; Burlina, A.; Chabriat, H.; Debette, S.; Enzinger, C.; Federico, A.; Filla, A.; Finsterer, J.; Hunt, D.; Lesnik Oberstein, S.; et al.
Abstract : Background and purpose: Guidelines on monogenic cerebral small‐vessel disease (cSVD) diagnosis and management are lacking. Endorsed by the Stroke and Neurogenetics Panels of the European Academy of Neurology, a group of experts has provided recommendations on selected monogenic cSVDs, i.e. cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL), autosomal dominant High Temperature Requirement A Serine Peptidase 1 (HTRA1), cathepsin‐A‐related arteriopathy with strokes and leukoencephalopathy (CARASAL), pontine autosomal dominant microangiopathy and leukoencephalopathy (PADMAL), Fabry disease, mitochondrial encephalopathy, lactic acidosis and stroke‐like episodes (MELAS) and type IV collagen (COL4)A1/2. Methods: We followed the Delphi methodology to provide recommendations on several unanswered questions related to monogenic cSVD, including genetic testing, clinical and neuroradiological diagnosis, and management. Results: We have proposed 'red‐flag' features suggestive of a monogenic disease. General principles applying to the management of all cSVDs and specific recommendations for the individual forms of monogenic cSVD were agreed by consensus. Conclusions: The results provide a framework for clinicians involved in the diagnosis and management of monogenic cSVD. Further multicentre observational and treatment studies are still needed to increase the level of evidence supporting our recommendations.